2013
DOI: 10.1128/iai.01396-12
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of the Role of yfiR in the Ability of Escherichia coli CFT073 To Control Cellular Cyclic Dimeric GMP Levels and To Persist in the Urinary Tract

Abstract: During urinary tract infections (UTIs), uropathogenic Escherichia coli must maintain a delicate balance between sessility and motility to achieve successful infection of both the bladder and kidneys. Previous studies showed that cyclic dimeric GMP (c-di-GMP) levels aid in the control of the transition between motile and nonmotile states in E. coli. The yfiRNB locus in E. coli CFT073 contains genes for YfiN, a diguanylate cyclase, and its activity regulators, YfiR and YfiB. Deletion of yfiR yielded a mutant tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 56 publications
4
35
0
2
Order By: Relevance
“…Additionally, ⌬yfiR strains were attenuated in their swimming motility (see Fig. S3B in the supplemental material), similar to results seen with E. coli CFT073 (52).…”
Section: Yfin and Yfir Can Control Cellulose Production In Uti89supporting
confidence: 75%
See 3 more Smart Citations
“…Additionally, ⌬yfiR strains were attenuated in their swimming motility (see Fig. S3B in the supplemental material), similar to results seen with E. coli CFT073 (52).…”
Section: Yfin and Yfir Can Control Cellulose Production In Uti89supporting
confidence: 75%
“…YfiN homodimerization is inhibited by the periplasmic protein YfiR (53,54). yfiRNB are in a single operon in E. coli, and YfiR and YfiN have similar activities in E. coli as those in P. aeruginosa (51)(52)(53)59). Previous work has also shown that the YfiN homolog AwsR controls Pseudomonas fluorescens cellulose and biofilm formation (60), and in Yersinia pestis, the YfiN and YfiR homologs, HmsD and HmsC, respectively, contribute to biofilm formation and the blockage of blood intake in the rat flea Xenopsylla cheopis (61,62).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mrkJ gene (located immediately upstream of mrkHI) encodes a phosphodiesterase enzyme that degrades intracellular c-di-GMP (8,26), while the yfiN gene (located in the yfiRNB operon) encodes a diguanylate cyclase that synthesizes c-di-GMP (8,34). To investigate whether changes in the concentration of intracellular c-di-GMP affect mrkH expression, we compared the levels of MrkH-mediated mrkH gene expression in ⌬mrkJ and ⌬yfiRNB K. pneumoniae mutants and their complemented plasmid strains by performing a real-time quantitative PCR assay.…”
Section: Expression Of Mrkhi Is Influenced By Mrkj-and Yfin-mediated mentioning
confidence: 99%